APLIKASI PEMBERIAN PUPUK KANDANG AYAM TERHADAP TIGA VARIETAS SORGUM - Wahida Wahida (AGRICOLA, 2012)
The aim of the research is to study the growth and production of three sorghum plant varieties in different doses of chicken manure. The research was conducted in experimental farm of Faculty of Agriculture, Hasanuddin University, Makassar. The research used split plot design. The main plot was sorghum plant variety consisting of three varieties, i.e. Numbu variety, Kawali variety, and Hegari genjah variety. Subplot was the dose of chicken manure consisting of four treatment dosages, i.e. 3.5 ton ha-1, 4.5 ton ha-1, 5.5 ton ha-1, and 6.5 ton ha-1. The results of the research reveal the Hegari Genjah variety is the highest plant height at the ages of 2, 4 and 6 MST, while Numbu variety is the highest plant at the age of 8 MST. Hegari Genjah variety given wide index of the highest leaf, and growth rate is relatively the highest. Kawali variety yields the highest net assimilation rate of the age of 2-4 MST and 4-6 MST and at age 6-8 MST Hegari early maturing varieties produce the highest net assimilation. Hegari Genjah Variety shows the longest panicle. Numbu variety gives the heaviest weight waste, i.e. the heaviest weight of 1.000 seeds